2020
DOI: 10.3390/mi11040409
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Experiment-Theory Comparison of Mid-Infrared Metasurface Perfect Absorbers

Abstract: Realisation of a perfect absorber A = 1 with transmittance and reflectance T = R = 0 by a thin metasurface is one of the hot topics in recent nanophotonics prompted by energy harvesting and sensor applications ( A + R + T = 1 is the energy conservation). Here we tested the optical properties of over 400 structures of metal–insulator–metal (MIM) metasurfaces for a range of variation in thickness of insulator, diameter of a disc and intra-disc distance both experimentally and numerically. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The surface roughness was not considered in the RCWA calculations in this study. However, previous studies have shown that the effect of surface roughness is significant in plasmonic absorbers [26,27]. Although the present calculations dealt with ideal conditions, our future works can deal with this problem by considering periodic structures that approximate the surface roughness in the RCWA calculations.…”
Section: Methodsmentioning
confidence: 96%
“…The surface roughness was not considered in the RCWA calculations in this study. However, previous studies have shown that the effect of surface roughness is significant in plasmonic absorbers [26,27]. Although the present calculations dealt with ideal conditions, our future works can deal with this problem by considering periodic structures that approximate the surface roughness in the RCWA calculations.…”
Section: Methodsmentioning
confidence: 96%
“…Additionally, the dephasing time of the inverted ETSC is a critical parameter that can be defined by taking into account the resonance narrowness as follows: Another important factor is V eff which represents the effective mode volume of the confined electromagnetic field in the cavity. Additionally, the effective mode volume is calculated according to V e f f = V ε(r)|E(r)| 2 dV max ε(r)|E(r)| 2 [34][35][36][37][38][39][40][41][42][43][44][45][46], where ε(r) is the dielectric constant, |E(r)| is the electric field strength and V is the volume encompassing the resonator with a boundary in the radiation zone of the cavity mode. As for Figure 11a, the minimum of V eff is 0.02 × 10 5 µm when h 2 = 50 nm.…”
Section: Bar Embedded the Inverted Etsc Configurationmentioning
confidence: 99%
“…The wavelength separation between the two resonances (~533 nm) is larger than the 3 dB linewidth of the orthogonal nanoantenna resonance on a glass substrate alone [33,34], which is beneficial for realizing wide-band strong nonlinearity. The interface plays an important role in the real fabrication of metamaterials [35,36], so the effect of interface roughness on linear and nonlinear properties should be considered in practical applications. We compare the transmission spectra of rough and flat AZO interfaces in the coupled structure, and the results are shown in Figure 3c: (1) the main resonance is redshifted, and the weak resonance is blueshifted in the rough interface.…”
Section: Linear Characteristic Analysismentioning
confidence: 99%